ANO7 rs77559646 Is Associated With First-line Docetaxel Treatment Response in Metastatic Castration-resistant Prostate Cancer - Kaikkonen E; Ettala O; Nikulainen I; Taimen P; Lehtinen I; Bostrom PJ; Kellokumpu-Lehtinen PL; Schleutker J (INT INST ANTICANCER RESEARCH, 2022)
Background: Identification of genetic prognostic biomarkers, such as germline variants, are urgently needed to choose optimal treatment for metastatic castration-resistant prostate cancer (mCRPC). Patients and Methods: The prognostic value of anoctamin 7 (ANO7) rs77559646 on docetaxel response was tested in a prospective PROSTY randomized trial and a retrospective Auria Biobank set. The variant rs77559646 was genotyped and its association with progression-free survival (PFS) and overall survival (OS) was tested. Results: In comparison with the non-carriers, the variant carriers had longer PFS (p=0.005) and OS (p=0.003) in the PROSTY cohort. In the retrospective cohort, there was a borderline association with PFS (p=0.09), but not in OS (p=0.9). In both cohorts, Cox regression multivariate models revealed that rs77559646 was an independent prognostic factor for favourable PFS. Conclusion: The rs77559646 was shown to be a prognostic germline biomarker for better response to docetaxel treatments. To our knowledge, this is the first time that a non-coding germline variant has been associated with chemotherapy of mCRPC.